2019
DOI: 10.3390/biom9090505
|View full text |Cite
|
Sign up to set email alerts
|

Elevated SH3BP5 Correlates with Poor Outcome and Contributes to the Growth of Acute Myeloid Leukemia Cells

Abstract: Current strategies are not especially successful in the treatment of acute myeloid leukemia (AML). The identification and characterization of oncogenes crucial to the survival and growth of leukemia cells will provide potential targets for the exploitation of novel therapies. Herein, we report that the elevated expression of SH3 domain-binding protein 5 (SH3BP5) significantly correlates with poor outcomes of AML patients. To test whether SH3BP5 contributes to the growth and survival of AML cells, we use the sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…Our analysis confirmed this role, and the STRING analysis also reveals that SLC44A1 may interact with SH3BP5 (Figure 2), an essential kinase for B-cell differentiation and proliferation [135]. In 2019, Li et al [90] reported that the elevated expression of SH3BP5 significantly also correlated with poor outcomes of acute myeloid leukemia patients [90]. Through the knock-down of SH3BP5, the authors demonstrated the inhibition of cell viability and the induction of apoptosis [90].…”
Section: Candidate Markers and Associated Functional Partnerssupporting
confidence: 70%
See 2 more Smart Citations
“…Our analysis confirmed this role, and the STRING analysis also reveals that SLC44A1 may interact with SH3BP5 (Figure 2), an essential kinase for B-cell differentiation and proliferation [135]. In 2019, Li et al [90] reported that the elevated expression of SH3BP5 significantly also correlated with poor outcomes of acute myeloid leukemia patients [90]. Through the knock-down of SH3BP5, the authors demonstrated the inhibition of cell viability and the induction of apoptosis [90].…”
Section: Candidate Markers and Associated Functional Partnerssupporting
confidence: 70%
“…It interacts with other choline transporters but also with a guanine nucleotide exchange factor (SH3BP5). Interestingly, the knockdown of SH3BP5 is known to induce apoptosis in leukemia cells [90] (Figure 2).…”
Section: Protein-protein Interaction Patterns To Infer On Gene Product Functionalitymentioning
confidence: 99%
See 1 more Smart Citation
“…Published studies of SH3BP5-AS1 are rare, while research on SH3BP5 has been reported frequently. High expression of SH3BP5 was proven to be associated with poor outcomes in acute myeloid leukemia patients [ 45 ]. Moreover, SH3BP5 was identified as an invasion- and proliferation-related gene of adrenocortical carcinoma [ 46 ].…”
Section: Discussionmentioning
confidence: 99%